Urbanity as an ethic. Reflections on the cities of the Arab world. - Lafi, Nora (Routledge, 2021)
Contemporary debates on urbanity generally focus on the evolution of the notion between modern and post-modern definitions, insisting on the threat that present-day trends toward a commodification of urban spaces represent as for the meaning of public spaces and the dissolution of civic values. The object of this chapter is to reflect on urbanity from a different point of view: different temporalities, different spaces and a definition that is centered on urban ethics. Under examination is the relationship between ethics and urbanity in an Islamic and Ottoman context. The intent is also to examine the evolution of this relationship at the moment of the impact with modernity, either under the form of an imperial Ottoman effort at modernization or under the ambiguous form of colonial modernity. Reflections in the chapter are based upon a study of Tunis, Aleppo and Cairo and particularly of the evolution of the notions of Hisba and maslaha al-‘amma between the middle-ages, the classical Ottoman period, the Ottoman modernizing reforms of the 19th century and the period of the French occupation after World War I. For each period, based on the study of local civic chronicles, local, imperial and consular archives and moral treaties, the chapter proposes an examination of the spatialization of urban ethics and of their civic content.
Keywords: Stadttyp; Islam; Städtebau; Urbanismus; Stadtgeschichte; Zusammenleben; Ethik; Stadtgeschichte; Mittelalter; Kolonialismus; Postkolonialismus